2008
DOI: 10.1002/jcp.21670
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and developmental potential of ovine bone marrow derived mesenchymal stem cells

Abstract: Since discovery, significant interest has been generated in the potential application of mesenchymal stem cells or multipotential stromal cells (MSC) for tissue regeneration and repair, due to their proliferative and multipotential capabilities. Although the sheep is often used as a large animal model for translating potential therapies for musculoskeletal injury and repair, the characteristics of MSC from ovine bone marrow have been inadequately described. Histological and gene expression studies have previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 83 publications
(98 reference statements)
13
126
2
Order By: Relevance
“…The multilineage differentiation ability, paracrine effects and immunomodulatory properties of MPCs make them an ideal for tissue engineering and regenerative purposes [5,7,[46][47][48]. Under appropriate conditions MPCs could be differentiated into a variety of mesenchymal tissues such as bone, cartilage, tendon, ligament, marrow stroma, muscle, fat and dermis [4,[49][50][51][52][53]. To induce fracture healing, MPCs are expanded ex vivo prior to their autologous grafting to the fracture site and differentiated into osteogenic lineages to promote bone regeneration [9,54].…”
Section: Cell-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The multilineage differentiation ability, paracrine effects and immunomodulatory properties of MPCs make them an ideal for tissue engineering and regenerative purposes [5,7,[46][47][48]. Under appropriate conditions MPCs could be differentiated into a variety of mesenchymal tissues such as bone, cartilage, tendon, ligament, marrow stroma, muscle, fat and dermis [4,[49][50][51][52][53]. To induce fracture healing, MPCs are expanded ex vivo prior to their autologous grafting to the fracture site and differentiated into osteogenic lineages to promote bone regeneration [9,54].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…The bone mineral density and bone strength in sheep is increased relative to human. Moreover, sheep models of critical size defects are extensively applied to evaluate cell-based therapeutic approaches using autologues, allogeneic or xenogeneic MPCs in combination with growth factors and different types of scaffolds to enhance bone regeneration showing significant advantages compared with cell-unloaded (empty) scaffolds [43,53,166,[169][170][171][172][173][174][175][176].…”
Section: Sheepmentioning
confidence: 99%
“…In all of these models, bony repair and/or bone growth defects that mimic the human clinical outcomes can be demonstrated. In particular, in the last decade more extensive work using a rat proximal tibial drill hole model has been performed , Arasapam et al 2006, Chung et al 2006, 2013a,b, 2014, Ngo et al 2006, McCarty et al 2009, Macsai et al 2011, which has demonstrated different phases of injury repair that lead to the undesirable bony repair, namely the inflammatory, the fibrogenic, and the osteogenic and remodelling phases, on days 1-3, 4-8 and 8 onwards respectively (Fig. 2).…”
Section: Growth Plate Injury Repair Responsesmentioning
confidence: 99%
“…Adult MSCs are capable of differentiating into cells of many tissues such as cartilage, bone, and fat. In addition, MSCs can be isolated from many different sources, including the periosteum, trabecular bone, adipose tissue, synovium, skeletal muscle, as well as the bone marrow , McCarty et al 2009. Interestingly, previous studies have observed that synovium-derived MSCs in particular had the greatest capability to enhance the chondrogenic differentiation potential when compared with any other mesenchymal tissue-derived cells (Sakaguchi et al 2005).…”
Section: Mscs For Growth Plate Injury Repairmentioning
confidence: 99%
See 1 more Smart Citation